Ukraine : Technical Assistance Report-Medium-Term Budget Framework and Fiscal Risk Statement. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance paper on Ukraine discusses medium-term budget framework (MTBF) and fiscal risk statement. In order to strengthen the medium-term orientation of the budget, the authorities have committed to implement a full-fledged MTBF as part of their Public Financial Management Reform Strategy (2017-21). The ability of the Ministry of Finance (MoF) to enforce compliance with ceilings during the annual budget will be critical to the success of the pilot exercise. The MoF will need to develop a robust report explaining the ceilings for cabinet discussion and for presentation to the legislature. The authorities have been taking steps to improve their understanding and disclosure of fiscal risks and have made significant progress with the inclusion of a summary fiscal risk statement in the draft Budget Declaration. The institutional structures to support fiscal risk analyses and disclosure are also yet to be established.